This book won't make you happy eight keys to finding true contentment. - FELICIANO, NIRO (BROADLEAF BOOKS, 2022)
When people find out she is a therapist, Niro Feliciano knows she isn't going anywhere anytime soon. At soccer games, at cocktail parties, in waiting rooms, people corner her and ask, Why am I so stressed? Is the way I feel normal? Why can't I just be happy? The truth is happiness is fleeting, and we are stressing ourselves out trying to achieve it. In This Book Won't Make You Happy, national media commentator and Psychology Today columnist Feliciano offers a path to something much more achievable and abundantly more satisfying: contentment. By incorporating eight simple postures rooted in cognitive behavioral science and mindfulness practices into our daily routines, we can move away from anxiety and toward balance and calm. Acceptance, gratitude, connection, a present-focused perspective, intentionality and priority, self-compassion, resilience, and faith: through these, practices we will overcome obstacles that hold us back from living full, meaningful, contented lives. Anxiety, stress, and grief aren't going away anytime soon, and this book won't make you happy. But, with wit and empathy, Feliciano leads you right past happy to calm. No matter how "happy" your life is, or isn't, you can reach a deeper, truer, and longer-lasting place of contentment.